Syzygium diversity in Gunung Baung, East Java, Indonesia - DEDEN MUDIANA (Society for Indonesian Biodiversity, 2016)
Mudiana D. 2016. Syzygium diversity in Gunung Baung, East Java, Indonesia. Biodiversitas 17: 733-740. Syzygium (Myrtaceae) consists of a lot of species which are widely distributed. One of the distribution areas is the Natural Park of Gunung Baung (TWA Gunung Baung) in Pasuruan, East Java. The results of exploration and characterization of known species show that there are six species of Syzygium known to grow in this region namely S. cumini, S. littorale, S. pycnanthum, S. polyanthum, S. racemosum, and S. samarangense. S. pycnanthum is the most frequently found in Gunung Baung. S. polyanthum and S. samarangense are the only species that are known to be cultivated. Four other species are wild and have not been explored for their potential utilization.